Correlation of clinical findings, collision parameters, and psychological factors in the outcome of whiplash associated disorders. Issue 5 (16th April 2004) - Richter, M; Ferrari, R; Otte, D; Kuensebeck, H-W; Blauth, M; Krettek, C
Abstract : Objective: To determine prognostic factors for the duration and severity of acute symptoms in subjects with grade 1 or 2 whiplash injuries. Methods: Collision victims presenting to a trauma centre with spinal pain or stiffness were assessed clinically (including a visual analogue scale (VAS)), radiologically, and psychologically (short form 36 (SF36), everyday life quality (EDLQ), pain control questionnaire (FSR)). Collision type and estimated ΔV (change in velocity of the occupant's vehicle) were also assessed. Assessment at six months involved VAS symptom rating, SF36, EDLQ, depression scale (CES-D), and impact of event scale (IES). Results: 43 consecutive collision victims (22 male, 21 female; mean age 29 years (range 19 to 72) with grade 1 or 2 whiplash associated disorders were assessed. Mean ΔV, available for 36 of 43 collisions, was 13.9 (5 to 30) km/h. Thirty two (74%) of the subjects were available for follow up at six months. The mean duration of symptoms was 28 (1 to 180) days in this group. No correlation was found between severity and duration of symptoms and the ΔV of collision or other collision parameters. Patients with initial pain VAS >5 or with duration of symptoms more than 28 days had significant changes in SF36, EDLQ, CES-D, and IES scores at six months, and had initial scores that were predictive of these outcomes. Conclusions: Psychological factors were found to be more relevant than collision severity in predicting the duration and severity of symptoms in collision victims with grade 1 or 2 whiplash associated disorders.